2022
DOI: 10.1021/acs.est.2c00776
|View full text |Cite
|
Sign up to set email alerts
|

Acetylacetone Interferes with Carbon and Nitrogen Metabolism of Microcystis aeruginosa by Cutting Off the Electron Flow to Ferredoxin

Abstract: The regulation of photosynthetic machinery with a nonoxidative approach is a powerful but challenging strategy for the selective inhibition of bloom-forming cyanobacteria. Acetylacetone (AA) was recently found to be a target-selective cyanocide for Microcystis aeruginosa, but the cause and effect in the studied system are still unclear. By recording of the chemical fingerprints of the cells at two treatment intervals (12 and 72 h with 0.1 mM AA) with omics assays, the molecular mechanism of AA in inactivating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…PCC6803 cells (Figure ). We found that the resulting differential metabolites were all located downstream of the Calvin cycle; namely, the glycolysis/gluconeogenesis pathway, pentose phosphate pathway, the tricarboxylic acid (TCA) cycle (including the branched glyoxylate cycle), and the amino acid metabolism were involved. …”
Section: Resultsmentioning
confidence: 99%
“…PCC6803 cells (Figure ). We found that the resulting differential metabolites were all located downstream of the Calvin cycle; namely, the glycolysis/gluconeogenesis pathway, pentose phosphate pathway, the tricarboxylic acid (TCA) cycle (including the branched glyoxylate cycle), and the amino acid metabolism were involved. …”
Section: Resultsmentioning
confidence: 99%
“…As critical biochemical reactions and defense responses in leaves were recognized to be activated prior to visible phenotypic end points, the inhibited plant growth is proposed to be an indication of the disturbance of photosynthesis, respiration, and transpiration processes. , Four parameters associated with photosynthesis, respiration, and transpiration of rice leaves were evaluated, including the net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), and water use efficiency (WUE). Little change in these indicators was observed in the treatment group of 1 μg/L BUVSs.…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we found that the simplest β -diketone, acetylacetone (AA), which is naturally present in fruits and vegetables as well as in treated sludge liquors, could enhance the redox conversion of quinones, either by acting as an electron donor for benzoquinone (BQ) or serving as an electron acceptor for hydroquinone (BQH 2 ) . Inspired by this observation, we have further demonstrated that AA could efficiently inhibit the growth of Microcystis aeruginosa (M. aeruginosa), which is one of the notorious bloom-forming and toxic cyanobacteria. , Unlike some other extensively used cyanocides, such as hydrogen peroxide, permanganate, and copper salts, AA works on M. aeruginosa in a nonoxidative way .…”
Section: Introductionmentioning
confidence: 96%
“…11 Inspired by this observation, we have further demonstrated that AA could efficiently inhibit the growth of Microcystis aeruginosa (M. aeruginosa), which is one of the notorious bloom-forming and toxic cyanobacteria. 12,13 Unlike some other extensively used cyanocides, such as hydrogen peroxide, permanganate, and copper salts, AA works on M. aeruginosa in a nonoxidative way. 12 The interference in electron transfer between two quinones (Q A and Q B ) in photosystem II was regarded as one of the function mechanisms of AA on M. aeruginosa.…”
Section: ■ Introductionmentioning
confidence: 99%